Sur l’espace des linéars d’appuis - Šinkūnas, J. (Lithuanian Mathematical Journal, 1966)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Ю. Шинкунас. О пространстве опорных линеаровJ. Šinkūnas. Apie atraminių linearų erdvę